The right to respect for family life, consent, minors and Gillick competence. (23rd September 2021) - Griffith, Richard
Abstract : Richard Griffith, Senior Lecturer in Health Law at Swansea University, discusses the statement made by the UK vaccines minister that healthy 12–15-year-olds could override their parents' decision on coronavirus vaccination